Rulership in Medieval East Central Europe
1 online resource.
Keywords: This book provides the first detailed overview of research on rulership in theory and practice, with a particular emphasis on the monarchies of Bohemia, Hungary and Poland in the High and Late Middle Ages. The contributions examine the legitimation of rule of the first local dynasties, the ritual practice of power, the ruling strategies and practices of power in the established monarchies, and the manifold influences on the rulership in East Central Europe from outside the region (such as from Byzantium, and the Holy Roman Empire). The collection shows that these ideas and practices enabled the new polities to become legitimate members of Latin Christendom.